A hydrostable cage-based MOF with open metal sites and Lewis basic sites immobilized in the pore surface for efficient separation and purification of natural gas and C2H2. Issue 11 (2nd March 2020) - Jiang, Zhenzhen; Zou, Ying; Xu, Tingting; Fan, Lihui; Zhou, Ping; He, Yabing
Abstract : A cage-based MOF displays excellent hydrolytic stability as well as promising potential for diverse gas separation applications. Abstract : Design and construction of stable adsorbents for efficient separation and purification of natural gas and C2 H2 is fundamentally important in the chemical industry, and hierarchical cage-based MOFs are attractive in this regard due to their intrinsic structural advantages. In this work, a cage-based MOF (termed ZJNU-15 ) assembled from a tetranuclear Cu4 O-based SBU and an amine-functionalized N, O-mixed donor ligand was solvothermally constructed. Single-crystal X-ray diffraction studies showed that the resulting MOF incorporates two different types of polyhedral cages in the entire network and bears incompatible open copper sites and uncoordinated amine groups immobilized in the pore surface. In view of its intriguing structural features, its gas adsorption properties with respect to C2 hydrocarbons, CO2, and CH4 were systematically investigated, revealing that it could achieve efficient removal of C2 hydrocarbons and CO2 from CH4 as well as separation of a binary C2 H2 –CO2 mixed gas, which is associated with natural gas and C2 H2 separation and purification. At 298 K and 1 atm, for equimolar binary components, the IAST-predicted adsorption selectivities for C2 hydrocarbons over CH4 are above 17.7, while the CO2 /CH4 and C2 H2 /CO2 adsorption selectivities are 5.0 and 4.4, respectively. Notably, stability studies showed that the framework maintained its structural integrity after being immersed in HCl/NaOH aqueous solutions within a pH range of 4–11 at ambient temperature for 24 h, indicating its good hydrolytic stability under harsh chemical conditions, which might lay a solid foundation for its practical applications.